Peran Orang Tua dalam Mendampingi Belajar Anak di Rumah di Era Covid - Marhamatul Awaliyah; Yusi Srihartini; Ahmad Syarif (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2022)
This research is a qualitative descriptive study that aims to determine the role of parents in accompanying children to study at home in the Covid era. This research method uses a qualitative approach with descriptive methods. The data were obtained by using questions in the form of parents' responses regarding learning at home, the obstacles faced by parents in accompanying children's learning at home, difficulties faced by children when studying at home and how parents overcome children's learning difficulties at home. The population of this study were parents of students who were affected by covid19. The conclusion of this study is that many parents assess that learning at home can strengthen the relationship with their children, even though there are various obstacles, as well as children who are not easy to do learning at home need adaptation and face many difficulties but these difficulties can be overcome by the parents of students. Keywords : The Role of Parents, Accompanying Learning, Children at Home, Covid -19